Beyond X-rays: an overview of emerging structural biology methods. Issue 2 (21st May 2021) - Schaffer, Jason E.; Kukshal, Vandna; Miller, Justin J.; Kitainda, Vivian; Jez, Joseph M.
Abstract : Structural biologists rely on X-ray crystallography as the main technique for determining the three-dimensional structures of macromolecules; however, in recent years, new methods that go beyond X-ray-based technologies are broadening the selection of tools to understand molecular structure and function. Simultaneously, national facilities are developing programming tools and maintaining personnel to aid novice structural biologists in de novo structure determination. The combination of X-ray free electron lasers (XFELs) and serial femtosecond crystallography (SFX) now enable time-resolved structure determination that allows for capture of dynamic processes, such as reaction mechanism and conformational flexibility. XFEL and SFX, along with microcrystal electron diffraction (MicroED), help side-step the need for large crystals for structural studies. Moreover, advances in cryogenic electron microscopy (cryo-EM) as a tool for structure determination is revolutionizing how difficult to crystallize macromolecules and/or complexes can be visualized at the atomic scale. This review aims to provide a broad overview of these new methods and to guide readers to more in-depth literature of these methods.